Analysis of load flow and short circuit studies of an offshore platform using ERACS software - K.N., Hasan; K.S.R., Rao; Z., Mokhtar (2008)

(untitled)
Load flow and short circuit studies are the two important power system analysis components to ensure the system upgrades, future upgrades and present distribution equipment meeting the present and future requirements. A number of power system analysis softwares are used to perform the analysis. This paper presents the analysis of load flow and short circuit studies of an offshore platform using ERACS software and analyses its performance by comparing with the existing EDSA software results. The EDSA software is commonly used in industries because of its accuracy and reliability while ERACS offers a user friendly with a powerful graphical user interface. The system analysis of an offshore platform, namely TBCP-A is performed to identify the peak load of full load and load shedding condition. The modeling of the TBCP-A network is then carried out using ERACS and the load flow study simulation is performed for three different scenarios, which are normal, maintenance services and emergency condition. The short circuit simulation is executed for two scenarios, namely during load exchange between two transformers and load exchanged between transformer and the emergency diesel generator. From the analysis, it is shown that no voltage violation occurs and all the bus bar ratings are sufficient except for one which is below the short circuit current rating. The ERACS software had produced an acceptable result where the deviation in both analyses is less than 7 % between the two soft wares for all scenarios. Â©2008 IEEE.